THE ROLE OF MINDFULNESS IN STRESS REDUCTION AND EMOTIONAL REGULATION (International Journal of Food and Nutritional Sciences, 2022)
Mindfulness has gained significant attention in recent years for its potential role in stress reduction and emotional regulation. This research paper explores the relationship between mindfulness practices and psychological well-being, focusing on their impact on stress management and emotional resilience. Drawing upon insights from psychology, neuroscience, and contemplative traditions, this study examines the mechanisms through which mindfulness techniques, such as meditation and mindful awareness, influence stress responses and emotional regulation processes. By synthesizing empirical research, theoretical frameworks, and clinical interventions, this paper seeks to elucidate the underlying mechanisms and outcomes of mindfulness-based interventions in promoting mental health and well-being.